Chloroplast phylogenomics of liverworts: a reappraisal of the backbone phylogeny of liverworts with emphasis on Ptilidiales. (22nd July 2019) - Yu, Ying; Yang, Jun‐Bo; Ma, Wen‐Zhang; Pressel, Silvia; Liu, Hong‐Mei; Wu, Yu‐Huan; Schneider, Harald
Abstract: As one of the four main lineages diverging from the early diversification of land plants, the phylogeny of liverworts holds the information about nearly 500 Myr of independent adaptation to changing environments. Thus, resolving the phylogenetic history of liverworts will provide unique insights into the successful diversification of early land plants in terrestrial ecosystems. However, the deep diverging events of this group remain incompletely resolved, such as the definite position of Ptilidiales. Here, we aimed to reconstruct the backbone relationships of liverworts using 84 protein‐coding chloroplast genes, a dataset comprising 35 representatives from all major lineages of liverworts, and three phylogenetic analyses, namely maximum parsimony, maximum likelihood and Bayesian inference. To test the impact of composition biases, the phylogenetic analyses were carried out using three alignments representing the same dataset either as: (i) nucleotides, (ii) amino acids, or (iii) recoded nucleotides applying ambiguity base code. Chloroplast genome data consistently supported the monophyletic origin of three major lineages in liverworts, as well as the majority of backbone relationships. Ptilidiales were found to be sister to Jungermanniales. The rapid accumulation of G/C tracks as a consequence of increased GC content is an important cause for the long branches inferred in this group. Our study not only provides empirical evidence to support the significance of plastid genome sequencing to reconstruct the phylogeny of this important plant lineage, but also suggests that the GC content has played a critical role in the evolutionary dynamics of plastid genomes in land plants.